Effect of kumquat (Fortunella crassifolia) pericarp on natural killer cell activity in vitro and in vivo. Issue 8 (3rd August 2015) - Nagahama, Kiyoko; Eto, Nozomu; Shimojo, Tomofumi; Kondoh, Tomomi; Nakahara, Keiko; Sakakibara, Yoichi; Fukui, Keiichi; Suiko, Masahito
Abstract: Natural killer (NK) cells play a key role in innate immune defense against infectious disease and cancer. A reduction of NK activity is likely to be associated with increased risk of these types of disease. In this study, we investigate the activation potential of kumquat pericarp acetone fraction (KP-AF) on NK cells. It is shown to significantly increase IFN-γ production and NK cytotoxic activity in human KHYG-1 NK cells. Moreover, oral administration of KP-AF significantly improves both suppressed plasma IFN-γ levels and NK cytotoxic activity per splenocyte in restraint-stressed mice. These results indicate that raw kumquat pericarp activates NK cells in vitro and in vivo . To identify the active constituents, we also examined IFN-γ production on KHYG-1 cells by the predicted active components. Only β-cryptoxanthin increased IFN-γ production, suggesting that NK cell activation effects of KP-AF may be caused by carotenoids such as β-cryptoxanthin. Graphical abstract: : Kumquat pericarp acetone fraction enhanced natural killer cell activity in human KHYG-1 natural killer cells and in restraint stress mice.